Changes in subjective wellbeing of prisoners on remand. Issue 2 (10th June 2019) - Bloem, Oscar; Bulten, Erik; Verkes, Robbert-Jan
Abstract : Purpose: Low levels of subjective wellbeing in prisoners may relate to mental health problems and difficulties in reintegration after imprisonment. The development of subjective wellbeing during imprisonment is mostly unclear. The purpose of this paper is to explore this development in a longitudinal study in association with mental disorders and socioeconomic factors. Design/methodology/approach: Subjective wellbeing was assessed via a visual analogue scale and retrieved at admission to remand prison and then again after four and eight weeks. Changes in subjective wellbeing between time-points were analyzed taking into account mental disorders and socioeconomic factors, which were assessed by use of the Mini International Neuropsychiatric Interview – Plus and the Camberwell Assessment of Need – Forensic Version, respectively. Findings: On average, subjective wellbeing declined directly after remand prison admission, but differences between individuals were found. At remand prison admission, subjective wellbeing significantly improved rather than declined in prisoners with alcohol and substance use disorders, housing problems, unemployment prior to incarceration and in relatively older prisoners. Other related factors did not add significance to this model. In contrast, during remand imprisonment subjective wellbeing displayed an overall increase. For this increase, no predicting factors were found. However, prisoners with an antisocial personality disorder are more at risk of experiencing a decrease in wellbeing during remand imprisonment. Originality/value: In general, the Dutch prison system appears not to result in a decrease in subjective wellbeing in prisoners suffering from a mental disorder during remand imprisonment.